Accountability and Community Participation in Village Fund Management: A Case Study of Midang Village, West Lombok - GALIH GALIHSTAN ABIMANYU (Journal of Economic Perspectives and Business Innovation, 2025)
AbstractAccountability and community participation are essential elements in ensuring effective village fund management and sustainable local development. This study examines how accountability mechanisms and public involvement are implemented in the management of village funds in Midang Village, West Lombok. Using a qualitative case study approach, data were collected through interviews with village officials, community members, and documentation analysis of financial reports and development programs. The findings indicate that transparent financial reporting, participatory planning forums, and community monitoring contribute to improved trust and more targeted development outcomes. However, challenges remain in administrative capacity, public awareness, and consistency in community engagement. The study concludes that strengthening institutional transparency and fostering active citizen participation are key to optimizing village fund governance and promoting inclusive rural development. Keywords: accountability, community participation, village fund management, local governance, rural development